Śrī Devanārāyaṇa kathā: Māravāḏa kā pāramparika gāyana - Bhopā, Hukmārāma; Gūjara, Moṭārāma; Malik, Aditya (South Asian studies, 2003)
Folk song on Devanārāyana, Hindu deity recited and performed in Rajasthan; transcription of the recordings
Parallelt.: Śrī Devnārāyaṇ kathā. - In Devanagari-Schr., Marwari; Einl.: Hindi in Devanagari-Schr. u. engl